The Letters of William Cullen Bryant Volume V, 1865-1871 - Voss, Thomas G.; Bryant, William Cullen (Fordham University Press, 1993)
On April 26, 1865, as Abraham Lincoln's funeral cortege paused in Union Square, New York, before being taken by rail to Springfield, Illinois, William Cullen Bryant listened as his own verse elegy for the slain president was read to a great concourse of mourners by the Reverend Samuel Osgood. Only five years earlier and a few blocks downtown, at Cooper Union, Bryant had introduced the prairie candidate to his first eastern audience. There his masterful appeal to the conscience of the nation prepared the way for his election to the presidency on the verge of the Civil War. Now, Bryant stood below Henry Kirke Brown's equestrian statue of George Washington, impressing Osgood as if he were "the 19tth Century itself thinking over the nation and the age in that presence." Bryant's staunch support of the Union cause throughout the war, and of Lincoln's war efforts, no less than his known influence with the president, led several prominent public figures to urge that he write Lincoln's biography. Oliver Wendell Holmes wrote him, "No man combines the qualities for his biographer so completely as yourself and the finished task would be a noble crown to a noble literary life." But Bryant declined, declaring his inability to record impartially critical events in which he had taken so central a part. Furthermore, while preoccupied with the editorial direction of the New York Evening Post, he was just then repossessing and enlarging his family's homestead at Cummington, Massachusetts, where he hoped his ailing wife might, during long summers in mountain air, regain her health. But in July 1866, Frances died of recurrent rheumatic fever, and, Bryant confessed to Richard Dana, he felt as "one cast out of Paradise." After France's death Bryant traveled with his daughter Julia for nearly a year through Great Britain and the Continent, where he met British statesman and novelist Edward Bulwer Lytton and French literary critic Hyppolyte Taine, renewed his friendship with Spanish poet Carolina Coronado, Italian liberator Giuseppe Garibaldi, and British and American artists, and visited the family of the young French journalist Georges Clemenceau, as well as the graves of earlier acquaintances Francis Lord Jeffrey and Elizabeth Barrett Browning. In his spare moments Bryant sought solace by beginning the translation of Homer, and Longfellow had found relief after his wife's tragic death by rendering into English Dante's Divine Comedy. Home again in New York, Bryant bought and settled in a house at 24 West 16th Street which would be his city home for the rest of his life. Here he completed major publications, including the Iliad and Odyssey of Homer and an exhaustive Library of Poetry and Song, and added to published tributes to earlier friends, such as Thomas Cole, Fenimore Cooper, and Washington Irving, memorial discourses on Fitz-Greene Halleck and Gulian Verplanck. In addition to his continued direction of the New York Homeopathic Medical college and the American Free Trade League, he was elected to the presidency of the Williams College Alumni Association, the International Copyright Association, and the Century Association, the club of artists and writers of which, twenty years earlier, he had been a principal founder and which he would direct for the last decade of his life.